2019
DOI: 10.1177/1179299x19896551
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural Response Alteration in Caenorhabditis elegans to Urine After Surgical Removal of Cancer: Nematode-NOSE (N-NOSE) for Postoperative Evaluation

Abstract: The technique used for cancer monitoring is essential for effective cancer therapy. Currently, several methods such as diagnostic imaging and biochemical markers have been used for cancer monitoring, but these are invasive and show low sensitivity. A previous study reported that Caenorhabditis elegans sensitively discriminated patients with cancer from healthy subjects, based on the smell of a urine sample. However, whether C. elegans olfaction can detect the removal of cancerous tumours remains unknown. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…It has been reported that the chemotaxis index becomes negative after surgery; therefore, it is speculated that some kind of tumor-associated substance is being detected by the nematodes. 24 On the other hand, there are still several unknown aspects of the test, for example, what specific substances the nematodes are reacting to and under what conditions the result should be considered positive. Therefore, the correlation between the index value and malignancy is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the chemotaxis index becomes negative after surgery; therefore, it is speculated that some kind of tumor-associated substance is being detected by the nematodes. 24 On the other hand, there are still several unknown aspects of the test, for example, what specific substances the nematodes are reacting to and under what conditions the result should be considered positive. Therefore, the correlation between the index value and malignancy is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that C. elegans could discriminate urine samples from patients with cancer from those obtained from healthy individuals [36]. The receiver operating characteristic (ROC) analysis has indicated that tests using C. elegans had a higher diagnostic ability than those using classical tumor markers; moreover, C. elegans showed a significant difference in behavior before and after tumor removal, suggesting that the C. elegans test will be useful in monitoring patients postoperatively [37]. Moreover, a relatively large study involving 180 urine samples from patients with gastrointestinal cancer and 76 samples from healthy participants has demonstrated that gastrointestinal cancer screening test has a high sensitivity, with a significant value of 0.80 in the ROC analysis, even in early-stage cancers [38].…”
Section: Smell Researchmentioning
confidence: 99%
“…elegans has been used to distinguish patients with cancer from healthy patients by using their sensitivity to smell on substances such as a urine samples [33]. The sensitivity and specificity of this detection ability have been optimized to analyze the chemotaxis or olfactory behavior response alteration, and a kit, known as Nematode-NOSE (N-NOSE) has been developed [34]. Receiver operating characteristic (ROC) analysis indicated that the N-NOSE was higher than that of classical tumor markers.…”
Section: Caenorhabditis Elegans (C Elegans)mentioning
confidence: 99%
“…Receiver operating characteristic (ROC) analysis indicated that the N-NOSE was higher than that of classical tumor markers. The N-NOSE showed different behaviors before and after tumor removal via surgical operation, suggesting its usefulness as a highly sensitive method to monitor patients postoperatively [34]. The results were confirmed through the analysis of a relatively large study of 180 urine samples from patients with gastrointestinal cancer and 76 samples from healthy participants, indicating the method's high sensitivity as a gastrointestinal cancer screening test, with a significant value of 0.80 in the receiver operating characteristic analysis, even in early stage cancers [35].…”
Section: Caenorhabditis Elegans (C Elegans)mentioning
confidence: 99%